Perilaku Body Shaming Pada Remaja Dalam Bermedia Sosial dalam Perspektif Ibnu ‘Asyur - Sri Lestari, Dian; Zaenatul Hakamah; Ahmad Syarifuddin; Nabila Rahmatul Husna; M. Qinthar Rahman (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
The development of information technology provides free access to all aspects of society to access social media as a means of communicating and socializing, especially among teenagers. Not only does it have a positive impact, in fact social media has a negative impact. In this writing, the author explains two problem formulations: first, regarding how body shaming is seen from the perspective of Tahir Ibnu Asyur in Surah al-Hujurat (39): 11. Second, this research also tries to contextualize Tahir Ibnu 'Asyur's interpretation of body shaming. This research uses the library study analysis method, where the author collects data from various sources such as books, books, tafsir books, and journals. In studying interpretation, the conceptual thematic method is used, where the author looks for verses that are relevant to the theme to be studied before carrying out analysis. The results of the analysis show that Tahir Ibnu 'Assyur considers reproaches to be verbal statements and the use of bad titles, but also notes that reproaches can manifest in bodily actions such as hand or eye movements, which can give rise to feelings of offense, as well as other bodily movements.